The Role of State Attorney Prosecutors to Restore State Financial Losses in Criminal Actions of Corruption to Make Justice - Widya Hari Sutanto; Umar Ma'ruf (Universitas Islam Sultan Agung, 2021)
Corruption is very detrimental to state finances or the country's economy and hinders national development, so it must be eradicated in order to create a just and prosperous society based on Pancasila and the 1945 Constitution of the Republic of Indonesia. This study uses a sociological juridical approach, which in this case is related to the role of the State Attorney General in recovering state financial losses with the specification of analytical descriptive research. The data used are primary and secondary data which will be analyzed qualitatively. The research problems were analyzed using the theory of justice and the theory of expediency. The results of the study concluded that the role of the Tegal State Attorney Office in an effort to recover state financial losses can be reviewed in the theory of return on assets and theory of justice which are the most important parts in seeking to recover state financial losses. The return of state financial assets that has been attempted by the Tegal City State Attorney's Office through efforts to confiscate or seize state assets is in accordance with the perspective of justice. Referring to the theory of justice and benefit by placing criminal and civil responsibility on the perpetrators of criminal acts of corruption and their heirs, it is hoped that the state financial losses that occur as a result of these acts can be fully returned as a form of justice for the perpetrators, the state and the community who have been injured.